Analysis of Employee Satisfaction Towards Salary, Position, Position Promotion, and Supervision - Evan Mardua Putra; Lise Asnur (International Journal of Social Science and Business, 2020)
Job satisfaction is a general attitude towards one's job, as the difference between the amount of reward received by workers and the amount of reward that is believed to be received. This research aims to analyze employee job satisfaction with salary, position, promotion, and supervision. This research is a quantitative study using a survey method. The population in this study were 70 people. The sample was obtained using a saturated sample technique. The data in this study were collected using a questionnaire and documentation. Data were analyzed using the principles of editing, tabulating, analyzing, interpreting, and concluding. The results showed that the salary indicator showed the respondents' assessment interpretation 49% agreed and 40% was sufficient; The position indicator shows the respondent's interpretation of 56% agree and 30% is sufficient; the job promotion indicator shows the interpretation of the respondents' assessment. 36% stated that the category was sufficient and 26% said the category did not agree; the supervision indicator shows the respondent's assessment interpretation. 57% agreed and 41% sufficient. So it can be concluded that overall employees show satisfaction at work.